Estudo da cinética e do equilíbrio da adsorção da cefamicina C em resina de troca iônica e simulação do processo contínuo - Rodriguez, Guilherme Youssef (Universidade Federal de São Carlos, 2011)
The cephamycin C (CefC) is a beta-lactam antibiotic produced from submerged and aerated cultures of Streptomyces clavuligerus. Acts as inhibitor of cell wall formation of Gram-negative bacteria and is resistant to the hydrolytic action of betalactamases enzymes. The literature presents few scientific results published regarding the purification of CefC, and the information is restricted to international patents. The first results regarding the production and purification of CefC are being released by the research group in Biochemical Engineering from the DEQ/UFSCar, in national and international conferences. Thus, given the importance of CefC, indispensable researches are needed particularly regarding the process of extraction and purification. In this work kinetics and equilibrium mathematical models were proposed to the adsorption of CefC on StreamLine QX-L ion exchange resin. Through experimental batch assays, the effects of pH (2.8, 4.7 and 6.8) and temperature (13°C, 20°C and 30°C) were studied, analyzing the intrinsic parameters calculated by nonlinear regression. The CARE model was adopted for continuous process and material balances were performed at each control surface. These balance equations were generated considering the models proposed in the batch tests. The general objective of this work is the simulation and optimization of the continuous process, applied to CefC. The simulations were carried both in transient and permanent modes. Steady state was optimized on performance parameters concentration factor (CF), purification factor (PF), efficiency (η) and productivity (σ), taking the system flows as independent variables. The numeric method adopted was the Sequential Quadratic Programing (SQP). It was found that the StreamLine QX-L resin adsorbs CefC around 0.25 mg/g, although higher values can be achieved with higher initial concentrations at pH 4.7. The best condition found was at pH 6.8 at 30°C, since it provides a reasonable maximum adsorption capacity without substantial affinity adsorbent-adsorbate loss. The batch models proposed agree with the tendency observed experimentally and the continuous process was simulated and optimized in the best condition. The calculations showed that it is possible to concentrate the CefC and operate the system in high yields, although these events do not occur concurrently.
Keywords: Engenharia bioquímica; Antibióticos; Produtos biotecnológicos - purificação; Modelagem; ENGENHARIAS::ENGENHARIA QUIMICA